Academic campus master plan, 1968, California State Polytechnic College - Corwin Booth and Associated Architects::::::::: (1968)
Each shaded region of the plan is categorized by its function and organization. This map was included in the 1968 Master Plan, designed by Corwin Booth and Associated Architects. See the full Master Plan at https://digital.lib.calpoly.edu/rekl-87902 (ua0079_2011-0048_0010)